Ethical Challenges in Neuromarketing : A Research Agenda - Alexander, Jacob; Shenoy, Veena; Yadav, Aradhna (Indian Journal of Marketing, 2019)
Neuromarketing is an emerging field which connects disciplines such as psychology, science, neurology, marketing, and neuroscience with economics. The main goal of neuromarketing is to explore how the brain is physiologically affected by various marketing strategies and advertising tools. The article discussed various neuromarketing techniques and their applications and aimed to examine the common ethical concerns of neuromarketing, emphasizing on the potential threats and risks to the consumers. A meta - analysis approach was used to capture the content of appropriate literatures and content analysis was done to support the views. As examined in the paper, neuromarketing studies the different emotions that are associated with human decision making and uses this information to improve the effectiveness of marketing. The benefits of this study can be taken to the marketing domain. This paper identified and addressed the qualitative impact of neuromarketing in different fields of advertisements and promotions. It also provided the metadata for future researchers to think about the universal code of ethics and objectives that can be implemented to promote the development of research in neuromarketing in a more positive light.